Utilizing Capa in Kali Linux for Wannacry Malware Identification and Analysis - Singgam, Pritiy; Nasution, Afifah Naila; Waruwu, Pedro Stella Mario Meyar (CV. Rayyan Dwi Bharata, 2025)
Purpose: This study aims to analyze the WannaCry ransomware using Kali Linux and the Common Access Platform Assistant (CAPA) method to provide a deeper understanding of the malware's attack tactics, capabilities, and behaviors. Methods/Study design/approach: The research was conducted by installing CAPA version 7.4.0 downloaded from GitHub, followed by file extraction and access permission configuration. The WannaCry malware was obtained from the